2017
DOI: 10.1177/2048872617695235
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognostic value of delirium in elderly patients with acute cardiac diseases admitted to two cardiac intensive care units: a prospective study (DELIRIUM CORDIS)

Abstract: Delirium is a common complication in elderly CICU patients, and is associated with a longer and more complicated hospital stay and increased short and long-term mortality. Our findings suggest the usefulness of a protocol for the early identification of delirium in the CICU. Clinicaltrials.gov: NCT02004665.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 35 publications
4
46
1
Order By: Relevance
“…For example, in the cardiac intensive care unit (ICU), delirium in patients 85 years old and above was present in 54% of subjects. [14][15][16] There were more comorbid conditions in the delirium group. The median Charlson index was 3 compared to 2 in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in the cardiac intensive care unit (ICU), delirium in patients 85 years old and above was present in 54% of subjects. [14][15][16] There were more comorbid conditions in the delirium group. The median Charlson index was 3 compared to 2 in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on elderly patients with acute coronary syndrome reported high rates of delirium, especially in critical‐care settings. For example, in the cardiac intensive care unit (ICU), delirium in patients 85 years old and above was present in 54% of subjects …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent prospective study of 726 European CICU patients reported that 15% of these patients were diagnosed with delirium during their hospital stay, a rate which was 50% in patients over the age of 85 years. 29 Another prospective study of 309 patients admitted to the CICU, found a 19% prevalence of delirium, with a 2-month incidence rate of 9% among those who were free of delirium at baseline. 30 Similarly, in the largest prospective study to date by Naksuk et al, the incidence rate of delirium among 11 079 patients was 8% while in the CICU.…”
Section: Epidemiologymentioning
confidence: 99%